2016
DOI: 10.1186/s12974-016-0732-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in peripheral axons delays disease progression in SOD1G93A mice

Abstract: BackgroundIncreasing evidence suggests that the immune system has a beneficial role in the progression of amyotrophic lateral sclerosis (ALS) although the mechanism remains unclear. Recently, we demonstrated that motor neurons (MNs) of C57SOD1G93A mice with slow disease progression activate molecules classically involved in the cross-talk with the immune system. This happens a lot less in 129SvSOD1G93A mice which, while expressing the same amount of transgene, had faster disease progression and earlier axonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 67 publications
5
98
0
1
Order By: Relevance
“…SCs in ALS expressed significant levels of CSF1, IL‐34, and SCF and spatially interacted with immune effector cells bearing CSF‐1R and c‐Kit, suggesting a complex cellular interplay leading to local inflammation. Previous studies have shown infiltrating macrophages, mast cells and neutrophils (Chiu et al, ; Nardo et al, ; Trias et al, ) as well as SC proliferation (Deng et al, ) in the sciatic nerve of rodent ALS models. Here, we identified that these immune effectors express CSF‐1R and c‐Kit in human ALS nerves.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…SCs in ALS expressed significant levels of CSF1, IL‐34, and SCF and spatially interacted with immune effector cells bearing CSF‐1R and c‐Kit, suggesting a complex cellular interplay leading to local inflammation. Previous studies have shown infiltrating macrophages, mast cells and neutrophils (Chiu et al, ; Nardo et al, ; Trias et al, ) as well as SC proliferation (Deng et al, ) in the sciatic nerve of rodent ALS models. Here, we identified that these immune effectors express CSF‐1R and c‐Kit in human ALS nerves.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies on ALS postmortem peripheral nerve pathology have provided scarce information on SC phenotypes (Nardo et al, ; Riva et al, ). We examined SCs by immunohistochemical analysis of three nerve specimens from ALS subjects and three control donors, as well as one ALS ventral root specimen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CNS, ALS is typically accompanied by neuroinflammation involving the emergence of reactive microglia, astrocytes, and aberrant glial phenotypes (3)(4)(5). Evidence also shows activation of circulating immune cells (6), as well as immune cell infiltration of the ALS-degenerating peripheral nerves containing motor axons (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…These cells are known to permeate the BBB in specific regions and actively interact with the degenerative cellular microenvironment surrounding motor neurons and motor axons [81, 131, 133, 134]. It is also possible that chronic neuroinflammation restricted to the CNS can extend to skeletal muscles and then to other organs, becoming a systemic inflammation [135, 136].…”
Section: Neuroinflammation In Neurodegenerative Diseasesmentioning
confidence: 99%